Expansion of highly activated invariant natural killer T cells with altered phenotype in acute dengue infection. (August 2016) - Kamaladasa, A.; Wickramasinghe, N.; Adikari, T. N.; Gomes, L.; Shyamali, N. L. A.; Salio, M.; Cerundolo, V.; Ogg, G. S.; Malavige, G. Neelika
Summary: Invariant natural killer T (iNKT) cells are capable of rapid activation and production of cytokines upon recognition of antigenic lipids presented by CD1d molecules. They have been shown to play a significant role in many viral infections and were observed to be highly activated in patients with acute dengue infection. In order to characterize further their role in dengue infection, we investigated the proportion of iNKT cells and their phenotype in adult patients with acute dengue infection. The functionality of iNKT cells in patients was investigated by both interferon (IFN)‐γ and interleukin (IL)−4 ex‐vivo enzyme‐linked immunospot (ELISPOT) assays following stimulation with alpha‐galactosyl‐ceramide (αGalCer). We found that circulating iNKT cell proportions were significantly higher ( P = 0·03) in patients with acute dengue when compared to healthy individuals and were predominantly of the CD4 + subset. iNKT cells of patients with acute dengue had reduced proportions expressing CD8α and CD161 when compared to healthy individuals. The iNKT cells of patients were highly activated and iNKT activation correlated significantly with dengue virus‐specific immunoglobulin (Ig)G antibody levels. iNKT cells expressing Bcl‐6 ( P = 0·0003) and both Bcl‐6 and inducible T cell co‐stimulator (ICOS) ( P = 0·006) were increased significantly in patients when compared to healthy individuals. Therefore, our data suggest that in acute dengue infection there is an expansion of highly activated CD4 + iNKT cells, with reduced expression of CD161 markers.